STUDI DIMENSI HUBUNGAN PEMASARAN DAN LOYALITAS PELANGGAN JASA SEKTOR PERBANKAN - Ermani Hadiyati (Jurnal Dinamika Manajemen, 2014)
The objective of this study is explainÂ  and analyse the simultaneous and partial influence on the marketing relationship dimension including trust, commitment, communication, complaint handling, and attitude toward the loyalty of banking sector service customer.Â  Data gathering used questionnaire. Data collected is verified with conducting validity and reliability test. Research results shows that the marketing relationship dimension embodies trust, commitment, communication, complaint handling, attitude that simultaneously and partially impact positively and significantly on banking sector service customer. The better the marketing relationship dimension the more loyal the customer in using banking sector service. A customer complaint handling is of marketing relationship dimension that has the greatest contribution on banking sector service customer loyalty. The faster is the complaint handling, the more loyal is the customer in using the banking service.Keywords: marketing relationship dimension, customer loyalty, banking sector service.